BALB/c mice infection with hybrid Leishmania (V.) guyanensis/L. (V.) shawi showed an intermediate virulence profile compared to parental species infections - Lima, Ana Carolina Stocco; Tomokane, Thaise Yumie; Rodrigues, Gabriela Fernandes; Alcântara, Larissa dos Santos; Campos, Marliane Batista; Pombo, Maíra; Laurenti, Márcia Dalastra; da Matta, Vania Lucia Ribeiro; Floeter-Winter, Lucile Maria; Corbett, Carlos Eduardo Pereira; Silveira, Fernando Tobias; Gomes, Cláudia Maria de Castro (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionHybridization events within the genus Leishmania have been documented; however, their impact on the infection dynamics of hybrids remains poorly understood. In this study, we compared the infection dynamics caused by a hybrid parasite, Leishmania (Viannia) guyanensis/Leishmania (Viannia) shawi, with those caused by its parental species, Leishmania (Viannia) guyanensis and Leishmania (Viannia) shawi, in BALB/c mice.MethodsBalb/c mice were inoculated with stationary-phase promastigote forms of each parasite. Lesion development and parasite load were monitored longitudinally, and cytokine production was assessed at 35 days post-infection (PI). ResultsThe infection with the hybrid parasite induced a more rapid and evident progression, attaining its largest dimension between days 14 and 28 days PI, followed by regression. In contrast, infection with L. (V.) guyanensis resulted in a continuous increase in swelling, whereas L. (V.) shawi caused only mild swelling. Parasite loads in skin and lymph nodes were comparable across groups, though the hybrid parasite exhibited a significant increase in parasite burden from day 35 PI onwards. DiscussionThe immunologic response of hybrid parasite infection was associated with reduced gamma interferon (IFN-γ) and elevated interleukin 4 (IL-4) production compared to parental species and controls (P < 0.05), with no significant differences observed in interleukin 12 (IL-12p40) or interleukin 10 (IL-10). Infection with L. (V.) guyanensis led to decreased IFN-γ in lymph nodes and increased IL-4 production in both skin and lymph nodes, whereas L. (V.) shawi infection did not significantly alter cytokine profiles. ConclusionTogether, these findings provide important insights into the distinct biological behavior of the Leishmania hybrid parasite and its parental species, underscoring the relevance of hybridization in shaping host-parasite interactions and advancing our understanding of leishmaniasis within complex eco-epidemiological settings.